Users’ Experiences of Mobile Financial Services at Rural Areas of Bangladesh - Rahman, Md. Mehadi (IAIN Surakarta, 2021)
Mobile Financial Services (MFS) is one of the new innovations of the modern financial system. It nowadays plays a crucial role in banking users’ day-to-day financial activities. This study investigates users’ experiences of MFS at rural areas of Bangladesh. Specifically, this study sought to gain an understanding of to what extent different factors positively or negatively influence users’ experience in using mobile financial services. This study was mainly a survey research. The data were obtained using a questionnaire from a total of 128 MFS users (102 male and 26 female) living in rural areas of Bangladesh who were conveniently chosen from five Upazilla in Barishal city. The findings suggested that MFS users in rural areas of Bangladesh have both positive and negative experiences toward the use of mobile financial services. This study further revealed six major factors that have influenced the users’ positive and negative experiences in general, i.e. perceived usefulness, perceived ease of use, perceived risk, trust, customer and MFS agent relationship, and perceived cost. It was found that the last factor (perceived cost) have generated the users’ negative experiences toward mobile financial services. Therefore, the government and MFS providers are encouraged to work together with some innovative strategies to change the users’ negative experiences into positive experiences of using the mobile financial services.